2003
DOI: 10.1007/s00040-003-0646-8
|View full text |Cite
|
Sign up to set email alerts
|

Finding its place in a competitive ant community: leaf fidelity of Camponotus sericeus

Abstract: Many species of ground nesting ants regularly visit extrafloral nectaries (EFNs) of the savannah tree Pseudocedrela kotschyi. The distribution of ants on the plants is mosaic-like, i. e. stable and predictable with different ant species dominating neighbouring trees. In order to examine whether foraging behaviour may influence the structure of these ant communities, we investigated individual foraging behaviour of Camponotus sericeus, the ant species with highest incidence on P. kotschyi trees in the study are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
12
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 40 publications
2
12
0
Order By: Relevance
“…Camponotus can forage singly or in small groups, with recruitment system (C. gigas, Pfeiffer and Linsenmair 2000;C. pennsylvanicus, Cannon 1998) and fidelity to host trees (C. sericeus, Mody and Linsenmair 2003), corroborating with our results (see Table 5). Although C. sericeiventris colonies at our study site had shown a large overlapping in the foraging area, they did not demonstrate a conspicuous aggressive behavior between individuals of distinct colonies.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Camponotus can forage singly or in small groups, with recruitment system (C. gigas, Pfeiffer and Linsenmair 2000;C. pennsylvanicus, Cannon 1998) and fidelity to host trees (C. sericeus, Mody and Linsenmair 2003), corroborating with our results (see Table 5). Although C. sericeiventris colonies at our study site had shown a large overlapping in the foraging area, they did not demonstrate a conspicuous aggressive behavior between individuals of distinct colonies.…”
Section: Discussionsupporting
confidence: 93%
“…The foraging radius found to C. sericeiventris in our study is similar to C. sericeus, also studied in savannas, which the home range was at least 26 m around the nest (Mody and Linsenmair 2003). Camponotus can forage singly or in small groups, with recruitment system (C. gigas, Pfeiffer and Linsenmair 2000;C.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…). The dominating ground‐nesting ants may systematically approach the tree crowns only in low numbers to search on the leaves for occasionally occurring arthropod prey and to regularly extract the extrafloral nectar (Mody and Linsenmair ).…”
Section: Discussionmentioning
confidence: 99%